Efektivitas Iklan Sirup Marjan Versi Cyberpunk Terhadap Generasi Z di Jawa Tengah - Ridanar, Malaika Mustikasari; Sari, Dewi Kartika; Herwandito, Seto (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Advertising plays a vital role as a marketing communication tool. It serves to introduce products, build brand image, and influence consumer purchasing decisions. However, its effectiveness must be evaluated to ensure that the message delivered is truly on target and the advertising objectives are achieved. This study examines the effectiveness of the Cyberpunk-themed Marjan Syrup advertisement broadcast on digital media, aiming to increase brand awareness and stimulate purchase interest among Generation Z in Central Java. The research method used is descriptive quantitative with a Customer Response Index (CRI) approach, which includes five stages: awareness, comprehend, interest, intentions, and action. A total of 400 Generation Z respondents who had seen the advertisement were selected using purposive sampling. The analysis results show a CRI score of 89.7%, indicating that the advertisement is quite effective in generating awareness, understanding, interest, purchase intention, and actual buying behavior. Thus, Marjan’s Cyberpunk advertising strategy proves relevant in influencing young audiences and can serve as a reference for future digital marketing campaigns.